The Impact of COVID-19 and the Practical Importance of Vaccinations and Nirmatrelvir/Ritonavir for Patients with Cardiovascular Disease - Marcin Wełnicki; Artur Mamcarz; Ernest Kuchar; Przemysław Mitkowski; Jerzy Jaroszewicz; Krzysztof Tomasiewicz; Mariusz Gąsior; Przemysław Leszek; Karol Adam Kamiński; Jacek Wysocki (Vaccines, 2025)
The COVID-19 pandemic posed a huge challenge to global health systems. In addition to searching for effective methods of treating and preventing infection with a new pathogen, we could once again observe that severe respiratory infection and its complications can be become a challenging problem for cardiac patients. Empirical observations are fully confirmed by the results of clinical trials. Patients with risk factors and already diagnosed with cardiovascular diseases are particularly exposed to the severe course of COVID-19, including death. That is why we consider it so important to promote vaccinations against COVID-19 as a safe and effective method of preventing serious infections in this special group of patients, in accordance with the updated recommendations of relevant experts. If an infection is detected, depending on its form and the risk of hospitalization, there are also several antiviral treatment strategies. Nirmatrelvir/ritonavir therapy is particularly effective in selected patient groups, but its use requires analysis of the cardiac pharmacotherapy regimen in the context of potentially significant drug interactions.